Revolutionizing Ease, Personal, and Reliable Travel Experience - Antonius Irwan; Theophila Mahesaprima P; Roozbeh Babolian Hendijani (Green Publisher Indonesia, 2024)
Indonesia has the potential for very abundant tourist areas. Each region or province still has many unexplored tourism potential or hidden gems. Indonesia consists of five main islands with 30 small islands, totaling 18,110 islands, with inhabited islands of around 6,000. Indonesia is one of the mega-biodiversity countries in the world, which means Indonesia has a high level of biodiversity. Indonesia has a rich cultural heritage; there are more than 300 ethnic groups, or 1,340 ethnic groups, in Indonesia. Information and communication technology (ICT) experience immense growth and change the way people search for information and purchase things through online networks, including travel booking. People easily search for any information regarding travel from multi channels available on their smartphone, including information about travel. This project is using a design thinking method which is a problem-solving approach that emphasizes empathy for the user, experimentation, and iteration. Each strategy needs clear performance measurements to make sure the business is doing well throughout its operations, both financially and non-financially. The business model of Trip ID seems promising as it ventures into a blue ocean with a unique product, targeting a niche market. The conversion process appears feasible and has shown promise. However, a significant challenge lies in gaining market share, as well-established competitors currently dominate 60% of the market.